Rubbish Bank, Resources, and The Velocity of Money at Medan Belawan Sub-District - Rangkuty, Dewi Mahrani; Br Naibaho, Yanti; Suhut, Anwar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Garbage is a serious problem in Indonesia, including in Medan Belawan District. The Rubbish Bank Program is present as a solution for Rubbish management and economic empowerment of the community. This research aims to analyze the concept of green economy through the Rubbish Bank program in Medan Belawan District.The research method used is qualitatively descriptive with a case study approach. Data is collected through observation, interview, and documentation. The data analysis technique used is thematic analysis. The Rubbish Bank Program in Medan Belawan District has provided economic, social, and environmental benefits. Economic benefits include increased community income, job creation, and savings in Rubbish transportation costs. Social benefits include increasing public awareness about the importance of good Rubbish management, and increasing public concern for the environment. Environmental benefits include reducing Rubbish generation, reducing environmental pollution, and preserving natural resources. The Rubbish Bank Program in Medan Belawan District is an example of the implementation of an effective and sustainable green economy concept. This program can be a model for other Rubbish management programs in Indonesia.